Lactosylceramide-enriched microdomains mediate human neutrophil immunological functions via carbohydrate-carbohydrate interaction - Iwabuchi, Kazuhisa; Nakayama, Hitoshi; Hanafusa, Kei (Glycoconjugate journal, 2022)
The innate immune system of mammalian cells is the first line of defense against pathogenic microorganisms. Phagocytes, which play the central role in this system, engulf microorganisms by a mechanism that involves pattern recognition receptors on their own surface and pathogen-associated molecular patterns (PAMPs) expressed by the microorganism. Components of PAMPs include glycans (polysaccharides) and glycoconjugates (carbohydrates covalently linked to other biological molecules). Pathogenic microorganisms display specific binding affinity to various types of glycosphingolipids (sphingosine-containing glycolipids; GSLs), and GSLs are involved in host–pathogen interactions. We observed that lactosylceramide (LacCer), a neutral GSL, binds directly to certain pathogen-specific molecules ( e.g. , Candida albicans -derived β-glucans, mycobacterial lipoarabinomannan) via carbohydrate-carbohydrate interaction. LacCer is expressed highly on human neutrophils, and forms membrane microdomains. Such LacCer-enriched microdomains mediate several important neutrophil functions, including chemotaxis, phagocytosis, and superoxide generation. Human neutrophils phagocytose pathogenic mycobacteria (including Mycobacterium tuberculosis ) through carbohydrate-carbohydrate interaction between LacCer on their own surface and mannose-capped lipoarabinomannan on the bacterium. During recognition of pathogen-specific glycans, direct association of LacCer-containing C24 fatty acid chain with Lyn (a Src family kinase) is necessary for signal transduction from the neutrophil exterior to interior. Pathogenic mycobacteria utilize a similar interaction to avoid killing by neutrophils. We describe here the mechanisms whereby LacCer mediates neutrophil immune systems via carbohydrate-carbohydrate interaction.